ANALISIS ILMIAH SURAH YASIN AYAT 80: API YANG TERBENTUK DARI KAYU HIJAU PERSPEKTIF AL-QUR`AN DAN SAINS - Ahmad Mujahid; Laila Astuti, M. Farid Ridha, Selvi Amanda (CV. Adiba Aisha Amira, 2025)
This article examines Surah Yasin verse 80 from the perspective of the Qur'an and science, focusing on the concept of fire formation from green wood. The study aims to identify the alignment between the interpretation of the verse and modern scientific knowledge regarding the combustion process and the chemical reactions that occur when wood burns. The analysis method employed includes a literature review of the Qur'an, as well as a review of scientific literature related to the physical and chemical properties of green wood. The findings indicate that although the verse was revealed in a different historical context, there is a strong relevance to scientific principles explaining the combustion process. This discovery not only reinforces the spiritual understanding of the sacred text but also demonstrates that science and religious teachings can complement each other. This research is expected to provide new insights for readers regarding the relationship between religious texts and science, as well as encourage further discussion on their integration in the context of education and research